2007
DOI: 10.1056/nejmsa064508
|View full text |Cite
|
Sign up to set email alerts
|

A National Survey of Physician–Industry Relationships

Abstract: The results of this national survey indicate that relationships between physicians and industry are common and underscore the variation among such relationships according to specialty, practice type, and professional activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
307
2
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 481 publications
(338 citation statements)
references
References 13 publications
26
307
2
3
Order By: Relevance
“…It also was shown that top orthopaedic implant manufacturers have shifted physician payments to more published surgeons and those with academic affiliations [23]. Physicians involved in training medical students or developing clinical practice guidelines have been shown to be more likely to report receiving payments from industry [9]. This is consistent with previously described methods of targeting highly-regarded ''thought leaders'' in various fields as spokespersons for industry [35].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…It also was shown that top orthopaedic implant manufacturers have shifted physician payments to more published surgeons and those with academic affiliations [23]. Physicians involved in training medical students or developing clinical practice guidelines have been shown to be more likely to report receiving payments from industry [9]. This is consistent with previously described methods of targeting highly-regarded ''thought leaders'' in various fields as spokespersons for industry [35].…”
Section: Discussionsupporting
confidence: 81%
“…As a result, industry payments to orthopaedic surgeons, mostly from medical drug or device manufacturers and group-purchasing organizations (GPOs) for consulting services, reimbursement for travel, or ownership royalties, are not irregular [23,33]. A nationwide survey of physicians of all specialties reported 94% of physicians received some form of payment from drug or device manufacturers during the previous year [9].…”
Section: Introductionmentioning
confidence: 99%
“…Despite our inability to describe the NMA membership roster non-responders, our response rates (53.1% from the AMA Masterfile, at worst 46.6% overall) are consistent with other recent national surveys of physicians on potentially sensitive topics (43%-53%). [36][37][38][39][40][41] Non-majority physicians in the US, regardless of specialty, geographic region, gender, years in practice, or age, continue to report high rates of workplace discrimination, comparable to rates reported over a decade ago. These findings suggest that efforts to address workplace discrimination have not been entirely successful, and new initiatives will be needed to achieve the goal of professional equity in medicine.…”
Section: Discussionmentioning
confidence: 99%
“…1 As many as 94% of US physicians maintain some financial relationships with the industry. 2,3 Driven by public interest in the disclosure of the extent of these financial relationships, the Sunshine Act is an important step in both quantifying these ties and shedding light on potential conflicts of interest and influence of the industry's payments on practice patterns. 4 Payments made to practitioners and medical staff by industry or group purchasing organizations are all reported and filed in the Act's database, which are publicly posted every year.…”
mentioning
confidence: 99%